Tingkat Minat Belajar Siswa dalam Materi Senam Irama(Anak Indonesia Hebat) dalam Pembelajaran PJOK - M Fahim Anasih; Bahtiar Hari Hardovi; Ahmad Bahriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify the level of students’ learning interest in the Anak Indonesia Hebat rhythmic gymnastics material in Physical Education. The research method used was descriptive quantitative with a Likert scale questionnaire that had been tested for validity and reliability, distributed to 36 students of class X4 at SMA Negeri Balung. The results showed that most students had a high level of learning interest with a combined percentage of agree and strongly agree responses of 71.59%, while students in the medium category reached 41.16% and the low category 6.93%. The conclusion of this study indicates that students’ learning interest in Anak Indonesia Hebat rhythmic gymnastics is generally high, although some still show doubt and require more varied learning strategies. Keywords: learning interest, physical education, rhythmic gymnastics, students